Case Report: Atypical acute compartment syndrome of the forearm in a child following minor trauma with consecutive osteomyelitis - Everaert, J.; Delafontaine, A.; Juanos Cabanas, J.; Leclercq, G.; Jennart, H.; Baillon, B. (Frontiers in Surgery, 2024)
Introduction: Forearm compartment syndrome (CS) in children is above all a clinical diagnosis whose main cause is traumatic. However, rarer causes such as infection can alter its clinical presentation. Clinical case: An 8-year-old boy has been seen in the emergency department complaining of severe forearm pain under a splint in a mild traumatic context. The previous radiological imaging examination three days before had not revealed any fractures.On admission, he presented with major signs of skin inflammation, loss of mobility, paresthesia and a significant biological inflammatory syndrome. The acute CS diagnosis has been made and was treated, but its atypical presentation raised a series of etiological hypotheses, in particular infectious, even if it remains rare. Complementary imaging examinations confirmed the presence of osteomyelitis of the distal radius as well as an occult Salter-Harris II fracture.Discussion: Beyond the classic "five P's of CS" -pain, paresthesia, paralysis, pallor and pulselessness-, CS's clinical presentations are multiple, especially in pediatric patients. In children, severe pain and increasing analgesic requirement must be indicators of a CS. We hypothesize that this patient sustained a nondisplaced Salter-Harris II fracture with a hematoma colonized by hematogenous osteomyelitis explaining its initial clinical presentation.Hematogenous osteomyelitis complicated by CS is rare and may be accompanied by a traumatic history. It's atypical presentation in pediatric patients requires vigilance and prompt diagnosis given the disastrous and irreversible complications.